CLINICAL CASE OF PREGNANCY AND BIRTH IN UTERINE FIBROIDS - G.T. RASULOVA; D.T. TURSUNOVA; SH.KH. VAKHOBOVA; F.K. ODINAEVA (Avicenna Tajik State Medical University, 2019)
In the article, a case of a favorable outcome of pregnancy and childbirth in a patient with large uterine fibroids is presented. Uterine fibroids, especially at large sizes, create unfavorable conditions for fetal development and its adequate growth. An important factor, in addition to size, is its localization relative to the uterine cavity, the place of the placenta. During the gestational process, it is important to be aware of all the features of tumor-like formation. Very significant in such cases is the system of redirecting patients to a higher level of perinatal care, where there are the necessary conditions for proper control of the condition of the fetus, the nature and size of the tumor, as well as the presence of specialists to carry out prompt delivery of any degree of difficulty and at any time of the day. Appropriate therapy, high-quality antenatal care, inpatient treatment for complications, pre-operative hospitalization, as well as surgical interventions (C-section and conservative myomectomy) allowed preserving pregnancy, preserving the organ and carrying out delivery in the full term of pregnancy by a viable fetus.